Drying Kinetics and Rehydration Characteristics of Convective Hot-Air Dried White Button Mushroom Slices - Doymaz, Ibrahim (HINDAWI LTD, 2014)
The effect of pretreatment (0.5% citric acid solution) and drying air temperature (40, 50, 60, and 70 degrees C) on drying characteristics of button mushroom slices was investigated in a cabinet dryer. The experimental results show that the drying temperature and pretreatment have significant effects on the moisture removal from mushroom. In addition, rehydration ratio of pretreated samples was higher than that of control ones. Four kinds of classical model were used to obtain moisture data and the logarithmic model was the best for representation of mushroom drying. The values of effective moisture diffusivity were found to range between 1.70x10(-10) and 7.12 x 10(-10) m(2)/s over the temperature range studied. The activation energy was found to be 35.04 and 37.21 kJ/mol for control and pretreated samples, respectively.
Keywords: PRETREATMENTS; VACUUM; DEHYDRATION; BEHAVIOR; MODELS; COLOR; FRESH; ACID; Chemistry